Religion and Marital Instability: Change in the 1970s? - Shrum, Wesley (Review of religious research, 1980)
The relationship between religious commitment, affiliation, and marital instability is investigated for the period 1972 to 1977 by means of log-linear methods. Three explanations for the increase in marital instability which refer to religious factors are examined: an overall decline in religiosity, changes in the nature of religious belief, and convergence of denominational differences. None of these are adequate: the preferred model suggests that the relationship between religiosity, as indicated by church attendance, and marital instability is unchanging, as is the relationship between affiliation and instability. The strength of the relationship between religiosity and instability does not depend on religious affiliation.